Human studies and user studies: a call for methodological inter-disciplinarity (Brenda Dervin) - Brenda Dervin (Information Research: An International Electronic Journal, 2003)
Drawing on extensive literature reviews focusing, in particular, on user (and audience) research in the fields of library and information science and communication studies, the author describes the increasing chaos of human studies and user studies--the plethora of theories, concepts, approaches, methods, and findings which plague researchers within and between fields and bewilder policy maker and practitioner observers. The origins and symptoms of these disciplinary overloads and the usual forms of inter-disciplinarity brought to bear on them are traced and the author argues that most usual approaches to inter-disciplinarity act as more of the same and contribute to overload conditions. She calls for a methodological approach to inter-disciplinarity based on fundamental communicative principles. For library and information science, which as a field has traditionally drawn on multi-disciplinary sources, the author cautions that as the field sets itself to the task of assisting the inter-disciplinary needs of its constituencies, it is especially important that the field also attend to inter-disciplinary needs within its own walls, between its many disparate and disconnected discourse communities.